PENINGKATAN KECEPATAN PROSES PENGERINGAN KARAGINAN MENGGUNAKAN PENGERING ADSORPSI DENGAN ZEOLIT - Djaeni, Mohamad (TEKNIK, 2012)
Drying carrageenan product still deals with low product quality and energy efficiency. The drying with airdehumidified by activated natural zeolite has a potential for drying the product. In this concept, air as dryingmedium was contacted with zeolite to reduce its relative humidity. Hence, the driving force of drying increasesand the process can be conducted at moderate temperature (40-60oC) to retain the quality. This research looksinto the effectiveness of adsorption dryer with zeolite for drying carrageenan. The natural zeolite is activated byheating 300-400oC for 2-3 hours. The zeolite is then used to dehumidify the ambient air as drying medium. Inthis work, the effect of drying temperature and carrageenan thickness on water content in carrageenan duringthe drying were studied. Results showed with air velocity 3.0 m/sec, thickness of carrageenan 1-2 mm,operational drying time 3 hours and air temperature 40-60oC, water content in carrageenan can be reducedfrom 82.0% to 25%. This result is very promising for industrial application.